Effects of deoxynivalenol-feed contamination on circulating LPS in pigs - Kahlert, Stefan (Innate Immun, 2019)
Low concentration of LPS can be detected in healthy mammals without triggering systemic inflammation. Here we analysed the influence of the mycotoxin deoxynivalenol (DON) on very low LPS concentrations and the role of DON in the physiology of pigs challenged with high artificial LPS dosage mimicking septic shock. Pigs were fed for 29 d with DON-contaminated (4.59 mg/kg feed) or control feed. Samples of control animals showed 6.6 ± 13.5 pg/ml LPS in portal and 3.1 ± 7.6 pg/ml LPS in jugular serum samples. In the DON fed group, 3.4 ± 7.2 pg/ml and 0.6 ± 0.8 pg/ml were detected. The differences were statistically not significant, indicating that DON is not a trigger for enhanced LPS transfer into the blood circulation. Next, pigs were challenged with 7.5 µg LPS/kg body mass via portal or jugular route. The application route did not significantly influence the LPS concentration. We expected higher circulating LPS concentrations in the presence of DON due to the additional stress of liver metabolism and reduced liver capacity to remove LPS from circulation. This scenario is supported by tendency. In summary, we found that DON is unlikely to influence LPS transfer in the gut; DON likely reduces the capacity for LPS removal in septic shock conditions.